From Commemoration to Conviction: Prosecuting Edgar Ray Killen for the "Mississippi Burning" Murders. (April 2015) - Whitlinger, Claire
Despite the growing number of civil rights era cold cases brought to trial over the past 20 years, surprisingly little social scientific research has examined how these cases emerged. This article examines one such case—the 2005 prosecution of Edgar Ray Killen for the 1964 murder of civil rights workers James Chaney, Andrew Goodman, and Michael Schwerner. Using event structure analysis and drawing on archival sources, media accounts, and interview data, this study finds that the trial would not have occurred without the 40th anniversary commemoration in Philadelphia, Mississippi. Furthermore, this study suggests that commemorations can serve as mechanisms connecting collective memory with broader social change by catalyzing mnemonic entrepreneurship and cultivating organizational structures and resources necessary to achieve positive legal outcomes. Such outcomes, however, can only occur when political opportunities are favorable and potential jurors have been primed through the "memory of commemoration."